Impact of counseling on the awareness of elderly women’s family about elder abuse according to the transtheoretical model - Sonia Oveisi; Shima Jahed; Forouzan Olfati (The Journal of Qazvin University of Medical Sciences, 2018)
Background: The population of the elderly has grown in recent years in the world and similarly in Iran. Objective: The aim of this study was to investigate the impact of counseling on the elderly women’s family and raising their awareness about the elder abuse. Methods: This clinical trial study was conducted from August to December 2017 in the health centers of Shahiryar, Tehran Province. Sixty five elderly women were selected by convenient sampling. Then, their first grade families were randomly assigned to two groups: intervention (n=34) and control (n=31). The intervention group received four sessions based on transtheoretical model. Modified questionnaire was evaluated elder abuse and the data analyzed by Pearson chi-square. Findings: The findings showed that counseling sessions, according to the transtheatrical model, can cause a significant reduction in negligence (P<0.005), psychological abuse (P=0.006) and financial harassment (P<0.005) in elderly women’s family. None of the elderly reported any physical abuse. Conclusion: The results showed that counseling based on transtheoretical model could be effective on raising awareness of the elderly women’s family. It is proposed to create a program of counseling for families, elderly women and increase sensitivity of this phenomenon.